THE ROLE OF ELECTRONIC PAYMENT METHODS IN ENHANCING INTERNAL CONTROL AND REDUCING FINANCIAL AND ADMINISTRATIVE CORRUPTION: THE GENERAL DIRECTORATE OF EDUCATION OF WASIT GOVERNORATE AS A MODEL - Mohammed Challoob Alwan (Scholar Express Journals, 2026)
This research aims to study the role of electronic payment in promoting financial integrity and transparency and reducing financial and administrative corruption by facilitating and accelerating internal control procedures and reducing red tape in government institutions, which in turn contributes to eliminating the manipulation of public funds by achieving better control. A questionnaire was used for a sample of account employees, auditors, and educational cadres (teachers, teachers, administrators) in the General Directorate of Education of Wasit, as well as auditors (who have dealt with this directorate from non-its affiliates). The study concluded with results and recommendations based on the questionnaire submitted and emphasizes the role of electronic payment methods to enhance transparency and improve control procedures, the lack of controls and policies to keep pace with this technological development, and the lack of involvement of employees in training courses that qualify them to work on these modern systems. The study recommended the need to issue clear controls and policies that regulate the electronic payment process, as well as the involvement of employees in training programs and education for these modern systems, as well as the modernization of the technical infrastructure in the directorate, in order to keep pace with the Requirements for electronic payment methods
Keywords: Electronic Payment; Internal Control; Financial and Administrative Corruption